(untitled) (Advances in Systems Science and Applications, 2016)
In his book "Capital in the XXI Century" by Thomas Piketty justified the two basic laws of capitalism. On the basis of these economic laws Thomas Piketty concluded destabilizing role of accumulated national capital. Based on his critical analysis this paper studied alternative ways of identification and knowledge of the objective laws’ system that would become the tools of detection imbalances in the economy and assessing the impact of the regulatory impacts on the development of a market economy. Develop an appropriate model for the analysis of regulatory impacts.